Therapy-Related Imaging Findings in Patients with Sarcoma - Bloem, Johan L.; Vriens, Dennis; Krol, Augustinus D.G.; Özdemir, Murat; Sande, Michiel A.J. van de; Gelderblom, Hans; Bovee, Judith V.M.G.; Hage, Jos A. van der; Noebauer-Huhmann, Iris M. (Seminars in Musculoskeletal Radiology, 2020)
Knowledge of imaging findings related to therapy administered to patients with sarcoma is pivotal in selecting appropriate care for these patients. Imaging studies are performed as surveillance in asymptomatic patients or because symptoms, including anxiety, develop. In addition to detection of recurrent disease and assessment of response to therapy, diagnosis of conditions related to therapy that may or may not need treatment has a marked positive impact on quality of life. The purpose of this review is to assist radiologists, nuclear physicians, and others clinicians involved in the diagnosis and treatment of these patients in recognizing imaging findings related to therapy and not to activity of the previously treated sarcoma. Imaging findings are time dependent and often specific in relation to therapy given.
Keywords: sarcoma; surgery; radiotherapy; oncology; radiology